Determinasi Kepatuhan Wajib Pajak dengan Kepercayaan Kepada Pemerintah dan Kondisi Keuangan sebagai Pemoderasi - Vince Ratnawati; Rina Lesmanasari; Ruhul Fitrios (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Riau, 2022)
This study describes research on Taxpayer Compliance in the Covid-19 pandemic. The purpose was to determine and analyze the effect of tax incentives and procedural justice on taxpayer compliance with trust in the government and financial condition as a moderator. The population of this study were UMKM taxpayers registered at the KPP Pratama Tampan and Senapelan Pekanbaru. The sampling technique used is incidental sampling. The data are collected through questionnaires that handed directly to the respondents and the returned and could be processed was 100 questionnaires. The data analysis technique used is SEM-PLS using WarpPLS 6.0 Software. The results showed that tax incentives and procedural justice had a effect on taxpayer compliance. The result also show trust in the government and financial conditions are moderating variables that strengthen the relationship between tax incentives and procedural justice on taxpayer compliance.